Late Secularization and Religion as Alien - Bruce, Steve 1954- (2015)
The argument that modernization and secularization are linked in some non-accidental and nontautological manner is sometimes rebutted with the assertion that the statistical evidence of decline in indices of interest in religion in the UK and elsewhere in the modern world is a mere trend that may be changed by a revival of interest in religion. This essay considers the obstacles to such a revival. It makes the case that ‘late secularization’ differs in three important ways from ‘early secularization’. The shared stock of religious knowledge is small, the public reputation of religion is poor, and religion is carried primarily by populations that are unusual in being drawn either from a narrow demographic or from immigrant peoples. Given the role of affective social bonds in religious conversion, the alien nature of the carriers of religion makes religious revival extremely unlikely.
Keywords: Conversion; Revival; Secularization